GENERALIZATION OF THE MATHEMATICAL MODEL OF ENERGY CONSUMPTION VERIFICATION AND REMOTE CONTROL (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Mathematical models for remote control optimize instrument performance, calibration, and measurement error minimization. The measurement system includes all devices and methods that implement the measurement process. In the mathematical model, the role of the structure of the system, the methods of operation and the error model is important.